CONTRIBUCION AL CONOCIMIENTO DE LOS PLASMOCITOS ERITROBLASTICOS - GONZALEZ GUZMAN, IGNACIO (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1946)
The clinical and pathological features in Huntington's chorea are discussed One case with the characteristic physical and mental symptoms is reported Histologically, the brain presented the most marked changes in the caudate nucleus and putamen with de
BOL INST ESTUD MED BIOL
Keywords: CONTRIBUCION, CONOCIMIENTO, PLASMOCITOS ERITROBLASTICOS; CIENCIAS MEDICAS; MEDICINA INTERNA; HEMATOLOGIA